2012
DOI: 10.1142/s0218127412502240
|View full text |Cite
|
Sign up to set email alerts
|

Chaos, Self Organized Criticality, Intermittent Turbulence and Nonextensivity Revealed From Seismogenesis in North Aegean Area

Abstract: Strong evidence is provided for significant far from equilibrium complex processes in the seismogenic layer of the North Aegean region (Greece), after applying modern nonlinear methods to various seismicity time series. The data used are subsets of the regional catalogue compiled in the central Seismological Station of Geophysics Department, Aristotle University of Thessaloniki and concern 4367 earthquakes of magnitude greater than 3.8, which took place during the period of 1968–2008. We present results, deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In a series of papers [5,[60][61][62] results were presented concerning seismogenesis in different Hellenic regions (land and sea of Greece), applying nonlinear analysis to various earthquake time series, such as magnitude, inter-event times, longitude and latitude time series. For the analysis, the model of the dripping faucet was used as a physical interpretation of the seismic process.…”
Section: Seismogenesismentioning
confidence: 99%
“…In a series of papers [5,[60][61][62] results were presented concerning seismogenesis in different Hellenic regions (land and sea of Greece), applying nonlinear analysis to various earthquake time series, such as magnitude, inter-event times, longitude and latitude time series. For the analysis, the model of the dripping faucet was used as a physical interpretation of the seismic process.…”
Section: Seismogenesismentioning
confidence: 99%
“…More specifically, it has been shown that the seismic process in the temporal and spatial domains may reveal features that are close to so-called low-dimensional dynamical structures, although the features of the behaviour in the energy domain appear close to randomness, i.e. representing high-dimensional dynamical processes (Goltz, 1998;Matcharashvili et al, 2000;Iliopoulos et al, 2012). This has been shown for whole catalogues as well as for their parts and for different time periods.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the results of analyses carried out to assess the dynamical features of the seismic process in terms of its separate domains (time, space, and energy) also indicate differences in behaviour (see e.g. Goltz, 1998;Matcharashvili et al, 2000Matcharashvili et al, , 2002Abe and Suzuki, 2004;Chelidze and Matcharashvili, 2007;Iliopoulos et al, 2012). More specifically, it has been shown that the seismic process in the temporal and spatial domains may reveal features that are close to so-called low-dimensional dynamical structures, although the features of the behaviour in the energy domain appear close to randomness, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was shown that in the temporal and spatial domains earthquakes' distribution may reveal some features of a low-dimensional, nonlinear structure, while in the energy domain (magnitude distribution) it is close to a random-like high dimensional process (Goltz, 1998;Matcharashvili et al, 2000). Moreover, according to present views, the extent of regularity of the seismic process should vary in time and space (Goltz, 1998;Matcharashvili et al, 2000Matcharashvili et al, , 2002Abe and Suzuki, 2004;Chelidze and Matcharashvili, 2007;Iliopoulos et al, 2012).…”
Section: Introductionmentioning
confidence: 99%